An Electrochromic Nickel Phosphate Film for Large-Area Smart Window with Ultra-Large Optical Modulation - Lei, Pengyang; Wang, Jinhui; Gao, Yi; Hu, Chengyu; Zhang, Siyu; Tong, Xingrui; Wang, Zhuanpei; Gao, Yuanhao; Cai, Guofa (Nano-Micro Letters, 2023)
Exploring materials with high electrochemical activity is of keen interest for electrochemistry-controlled optical and energy storage devices. However, it remains a great challenge for transition metal oxides to meet this feature due to their low electron conductivity and insufficient reaction sites. Here, we propose a type of transition metal phosphate (NiHPO4·3H2O, NHP) by a facile and scalable electrodeposition method, which can achieve the capability of efficient ion accommodation and injection/extraction for electrochromic energy storage applications. Specifically, the NHP film with an ultra-high transmittance (approach to 100%) achieves a large optical modulation (90.8% at 500 nm), high coloration efficiency (75.4 cm2 C−1 at 500 nm), and a high specific capacity of 47.8 mAh g−1 at 0.4 A g−1. Furthermore, the transformation mechanism of NHP upon electrochemical reaction is systematically elucidated using in situ and ex situ techniques. Ultimately, a large-area electrochromic smart window with 100 cm2 is constructed based on the NHP electrode, displaying superior electrochromic energy storage performance in regulating natural light and storing electrical charges. Our findings may open up new strategies for developing advanced electrochromic energy storage materials and smart windows. Highlights: 1 Transition metal phosphates were first developed for the electrochromic application. 2 The obtained NiHPO4·3H2O film achieves an ultra-large optical modulation of 90.8%, and the electrochromic mechanism is systematically elucidated using in situ and ex situ techniques. 3 A large-area electrochromic smart window with 100 cm2 is constructed, which displays superior performances in regulating natural lighting and storing electrical charges.